Problematika Hukum dalam Pengelolaan Zakat dan Wakaf Uang di Indonesia - Hadi, Solikhul (Sharia Faculty Islamic Economic Law Study Department, 2025)
Previous studies on the management of zakat and waqf in Indonesia tend to use an objective perspective and do not accommodate subjective perspectives. This study aims to complement the shortcomings of previous studies by analyzing the problems faced in the management of zakat and cash waqf in Indonesia from a subjective perspective, namely by involving a society with their culture. In line with that, two questions are formulated: First, how is the implementation of zakat and cash waqf management in Indonesia? And second, what are the problems faced in the implementation of zakat and cash waqf management in Indonesia? This study is field research with a qualitative-subjective approach. From the results of the study found two answers to the problem formulation. First, the management of zakat and cash waqf in Indonesia is quite adequate in terms of zakat and cash waqf regulations. However, in terms of achieving philanthropy from the community, it is not optimal. Second, the main obstacles in zakat management in Indonesia are the lack of management effectiveness, the lack of human resources (HR), and the still low level of awareness of muzakki. And the main obstacles in the management of cash waqf are three things, namely: weak literacy, weak trust and limited number of fundraisers spread throughout Indonesia.